Evaluation of Nonlinear Fracture Quantities in Lime-Pumice Mixtures - Eren, Erkin; Ince, Ragip (ISRES Publishing, 2025)
The tests on fracture mechanics of quasi-brittle materials until the 1970s indicated that linear elastic fracture mechanics (LEFM) was not valid for cement-based materials such as mortar and concrete. This inapplicability of LEFM is due to the existence of an inelastic zone, which is also so-called fracture process. Therefore, numerous non-Hookean fracture models have been introduced to evaluate fracture quantities in quasi-brittle materials. According to the two-parameter model (TPM) in concrete fracture, a free crack propagates unstably whenever the stress intensity factor and the crack tip opening displacement are equal to their threshold values, such as Mode I fracture toughness and critical crack tip opening displacement, respectively. In this study, beams, cubes and square prismatic specimens with three different initial crack lengths were produced to calculate fracture quantities of lime-pumice mixtures. Beams with a maximum aggregate diameter (g) of 4 mm were kept in the mold for 28 days while cubes with g=4 mm and square prismatic specimens with g=16 mm were saved in the mold for 90 days. The fracture quantities of the mixtures were evaluated by employing the modified peak load method, which was recently derived to determine fracture properties of TPM. © 2025 Published by ISRES.
8th International Conference on Technology, Engineering and Science, IConTES 2025 -- 12 November 2025 through 15 November 2025 -- Antalya -- 347549
Keywords: Fracture mechanics; Lime; Pumice; Two-parameter model